Association between Reperfusion Renal Allograft Biopsy Findings and Transplant Outcomes - Mohan, Sumit; Campenot, Eric; Chiles, Mariana C; Santoriello, Dominick; Bland, Eric; Crew, R John; Rosenstiel, Paul; Dube, Geoffrey; Batal, Ibrahim; Radhakrishnan, Jai; Sandoval, P Rodrigo; Guarrera, James; et al. (Journal of the American Society of Nephrology, 2017)
Biopsy findings at the time of procurement of deceased donor kidneys remain the most common reason cited for kidney discard. To determine the value of renal allograft histology in predicting outcomes, we evaluated the significance of histologic findings, read by experienced renal pathologists, in 975 postreperfusion biopsy specimens collected from 2005 to 2009 after living donor ( =427) or deceased donor ( =548) renal transplant. We evaluated specimens for the degree of glomerulosclerosis, interstitial fibrosis and tubular atrophy, and vascular disease; specimens with a score of 0 or 1 (scale, 0-3) for each parameter were considered optimal. Overall, 66.3% of living donor kidneys and 50.7% of deceased donor kidneys received an optimal histology score ( <0.001). Irrespective of donor status, suboptimal kidneys came from older donors with a higher incidence of diabetes mellitus, hypertension, and obesity and a higher mean kidney donor risk index (all <0.001). Death-censored outcomes after transplant differed significantly between optimal and suboptimal kidneys only in the deceased donor transplants ( =0.02). Regardless of histologic classification, outcomes with deceased donor kidneys were inferior to outcomes with living donor kidneys. However, 73.2% of deceased donor kidneys with suboptimal histology remained functional at 5 years. Our findings suggest that histologic findings on postreperfusion biopsy associate with outcomes after deceased donor but not living donor renal transplants, thus donor death and organ preservation-related factors may be of greater prognostic importance. Discarding donated kidneys on the basis of histologic factors may be inappropriate and merits further study.